Features, uncertainities and utopian sides of the Italian school between XIX and XX centuries. On a volume by Saverio Faustino de Dominicis - Stizzo, Fabio (Rivista di Storia dell’Educazione, 2018)
Gaps and deficiencies in the Italian education system kept coming out in the years between the Nineteenth and Twentieth century. Positivist pedagogue Saverio De Dominicis was a remakable interpreter of the ideological and scientific demands of this time. In this article, his work Linee di Pedagogia Elementare per le Scuole Normali e per i Maestri secondo i vigenti Programmi Governativi (1897, Lines of Elementary Pedagogy for Normal School and for teachers according to Governmental Programs in force) is analised in order to focus on the most advanced theories and the counter-current proposals he sketched out in order to get a civil and social improvement of all the Kingdom of Italy using public school.